Analysis of the influence of infeed rate and cutting fluid on cylindrical grinding processes using a conventional wheel - Bianchi, Eduardo Carlos [UNESP]; Franzo, Carolina Grimm [UNESP]; Aguiar, Paulo Roberto De [UNESP]; Catai, Rodrigo Eduardo [UNESP] (ABM, ABC, ABPol, 2004)
New worldwide trends such as globalization have rendered grinding processes increasingly important for industry, making it essential to perform in-depth studies of variations in grinding process parameters in the pursuit of greater cost effectiveness. This paper presents a comparative analysis of three different infeed rates, using a conventional grinding wheel on quenched and tempered D2 steel workpieces. Higher infeed rates are known to be correlated with shorter grinding times, rendering the process more economically attractive. Two different coolant fluids, 5% emulsion and pure oil, were used. The tests were carried out using the smallest possible amount of coolant and an optimized 5 mm diameter nozzle. The parameters analyzed were tangential force, specific energy, acoustic emission, roundness error and surface roughness. The surfaces of the workpieces were also examined by scanning electron microscopy (SEM). The results revealed that increased infeed rates could reduce processing times without compromising the quality of the workpiece profile, thereby reducing the cost of the process. The best cutting fluid, albeit more harmful to human health and less environmentally friendly, was found to be pure oil.
Keywords: Cylindrical Plunge Grinding; Infeed Rate; Cutting Fluid; SEM and Roundness Error